Design of Microstrip antenna by Integrating Octagonal Patch Configuration for UWB Application - S. Patil; A. Naik (Advanced electromagnetics, 2025)
This work proposes gain enhancement of the microstrip antenna to use in applications operated in UWB spectrum. The antenna structure comprises integrated octagonal shaped radiator and slotted ground plane fabricated on easily available FR4 substrate. The 50 Ω microstrip line fed octagonal shaped microstrip antenna is simulated by using Ansys high-frequency structure simulator. The radiator is modified by integrating patch configuration to achieve gain improvement. The modified antenna is modelled by vertically integrating two octagonal shaped patches, etching off small two square slots and small square slot of dimension 1 mm × 1 mm positioned at the mid width of the ground. The designed MI-OMSA structure is fabricated on double sided copper flame retardant epoxy glass composite dielectric substrate having size of 37 mm × 40 mm and tested by using vector network analyzer. The optimized MI-OMSA structure provides minimum return loss characteristically below -10 dB over 2.42 – 11.72 GHz frequency range, covering bandwidth of 9.31 GHz. The peak gain observed at 8.2 GHz is 6.7 dB. The structure demonstrates constant group delay over the operating spectrum. An ultra-wideband performance is achieved as antenna resonates at four frequencies. The antenna structure offers radiation pattern of omnidirectional and hence most fit for use in UWB applications. An UWB application, breast cancer detection is tested using proposed structure.